Choosing the denture occlusion - A Systematic review - Ritika Bhambhani; Shubha Joshi; Santanu Sen Roy; Aditi Shinghvi (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study is to acquire evidence for the choice of occlusion with anatomic/modified anatomic teeth in complete denture prosthesis. Settings and Design: Systematic review following PRISMA guidelines. Materials and Methods: The study reviewed original articles on various occlusal schemes bilateral balance occlusion (BBO), lingual occlusion (LO), Canine guided occlusion (CG), posterior group function occlusion (PGFO) have been applied to the complete dentures and were analyzed for the objective or subjective or both evaluations. The data were collected in standard format with the needed information such as year of publication, type of study, occlusal schemes compared, test methodology used, sample size for experiment and control, assessment of retention, stability, and other factors which determine the quality of life and period of follow-up. The risk of bias was calculated using tools RoB2.0 and robvis. At all stages, the inclusion and exclusion of studies were discussed among the reviewers. Statistical Analysis used: Due to the heterogeneity in the data of the included studies no statistical analysis was used. Results: Of the 1896 articles screened only 17 studies were included in the systematic review. These were discussed amongst the reviewers regarding the various occlusion schemes used. The subjective and objective criteria used in the studies was tabulated separately. They were then analyzed for the risk of bias using the robvis 2 tool. Conclusion: No scheme is more superior to the other with the anatomic tooth forms. The use of alternative unbalanced schemes produces a similar satisfactory clinical outcome. The ridge classification also has a significant role to play in the preference for an occlusal scheme.